STRATEGI KOMUNIKASI PEMASARAN PT. DIGITAL KREASI INDONESIA DALAM MENINGKATKAN SUBSCRIBER CHANNEL NUSSA OFFICIAL DI YOUTUBE MELALUI INSTAGRAM - Wishnu Mahendra Putra Mangarapian (Universitas Mercu Buana, 2020)
Marketing communication strategy is a process in which the company plans things to be implemented to achieve company goals. This research aims to describe the marketing communication strategy carried out by PT. Digital Kreasi Internasional in increasing subscribers to the Nussa Official channel on Youtube through social media Instagram for the 2019 period. This research uses a constructivist paradigm, with a case study method, a descriptive-qualitative approach. The results of the study illustrate the stages of the marketing communication strategy carried out by PT. Digital Creation International in 2019, namely, first starting from small research (not carried out massively), secondly carrying out direct implementation (creating content), third doing analysis as well as strategic planning from the results of content that have been broadcast to the public, fourth re-implementation in which there are execution media and monitoring, finally, the company conducts an evaluation. The company uses a pull marketing communication strategy. The effort is being made to update the content on Youtube, Instagram, and website platforms regularly according to market demand.